Analisis Kadar Kafein pada Kopi Liberika (Coffea liberica) Menggunakan Metode Spektrofotometri UV-Vis - Azmi Prasasti; Anung Kustriyani; Abi Mas Udianto; Ulil Delafani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Coffee Liberica (Coffea liberica) is one of the coffee varieties that has the potential to be developed, but information on the effect of roasting levels on caffeine content is limited. Meanwhile, caffeine levels are an important parameter that affects quality and sensory characteristics. This study aims to qualitatively identify the presence of caffeine and quantitatively determine caffeine levels in liberica coffee with different roast levels, namely light, medium, and dark roast. The research was conducted experimentally in the laboratory using the Qualitative Test of the Parry method and the quantitative test of the UV-Vis Spectrophotometry method. The sample was in the form of liberica coffee beans at three roasting levels and was repeated three times. The results of the qualitative test showed that all samples of liberica coffee at the three levels of positive roasting contained caffeine which was characterized by the formation of a green color in the Parry test. The results of the quantitative analysis showed that the highest caffeine level was found at the light roast level of 116.412 mg/g, followed by medium at 102.381 mg/g, and the lowest at dark roast at 91.036 mg/g. The decrease in caffeine content as the temperature increases and the length of the roasting time shows that the roasting process has a significant effect on the stability of caffeine. The results of this study are expected to make a scientific contribution to the development of the chemical study of Liberica coffee, as well as become a practical reference for coffee industry players in determining the roasting level according to the characteristics of caffeine.